A disciplina de química na Escola Normal De São Paulo: 1880 - 1896 - Cardoso, Giseli De Oliveira [UNIFESP] (2019)
Educational history theorists such as André Chervel, Dominique Julia, Antonio Viñao and Ivor Goodson argue that research in the history of school subjects provides an internal look at school by addressing its practices and behaviors, helping to elucidate elements of school culture. Such a conception helps us to think about how chemistry teaching was established, in the teaching practices already proposed, in the construction of our relationship with science and technology. In this research, which aims to raise elements of school culture by analyzing the history of the Chemistry discipline of the Escola Normal de São Paulo, the study was conducted through documents such as crafts, laws, programs, meeting minutes, reports, photographs, inventories. , newspaper publications, among other documents, that is, materials linked to the discipline that constitute the school collection and consequently the research corpus. The documentary analysis allowed us to sketch the history of the chemistry discipline and consequently the history of the Escola Normal, since one cannot be detached from the other. The school went through three foundations, and only in the last one in 1880 did chemistry teaching be included in the curriculum. This reflects a political and social change demanded by the society of the time that wished to have a teacher who had basic scientific notions. This conception is accompanied by the requirement that the normalists dominate the intuitive method, and the scientific method was seen as a natural element of this teaching methodology, which made the scientific disciplines receive considerable investment. The first of these was when Professor Paulo Bourroul, acquires the Chemistry Lab and the Physics Office, which provided structure for experimental classes. The teachers who occupied the 5th chair exerted strong influences in the chemistry discipline, impressing their ideals in the construction of the programs. The changes in teaching programs and purposes in the chemistry discipline also accompany the political changes that occur during the study period, in the early years of the republic, the school becomes a symbol, and the chemistry discipline receives investment in infrastructure, making In its more extensive and encyclopedic teaching plan, however, experimental practices play a key role in teaching the subject with its own spaces and classes. The teaching of chemistry was established with a process of valorization of experimental practices, ideals prevailing until the present day for the teaching of science.